Impact of a mid-test warning on the personality-cognitive ability relationship in a field setting. (March 2021) - Zheng, Lu; Li, Hairong; Hua, Jing; Zhao, Guoxiang; Li, Yongxin; Wang, Minghui; Fan, Jinyan
Abstract: Researchers recently developed new mid-test warning faking-mitigation procedures to address the faking issue found in personality tests. The use of warning messages may unexpectedly make faking on personality tests a more cognitively loaded task, resulting in a positive relationship between personality scores and cognitive ability. The primary purpose of the present research is to investigate the effect of a mid-test warning on the personality-cognitive ability relationship. Graduate school applicants at a large public university in China ( n  = 2032) went through a test-warning-retest procedure. A true experimental design was used wherein each participant received a mid-test warning or a control message randomly. Results indicated that the mid-test warning significantly lowered personality scores over retesting, whereas the control message had little impact on applicants. The mid-test warning, however, did not induce positive and significant correlations between measures of personality and cognitive ability.